2018
DOI: 10.1021/acs.analchem.8b00664
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis Sensitivity Enhancement Based on Adaptive Moving Average Method

Abstract: In the present work, we demonstrate a novel approach to improve the sensitivity of the "out of lab" portable capillary electrophoretic measurements. Nowadays, many signal enhancement methods are (i) underused (nonoptimal), (ii) overused (distorts the data), or (iii) inapplicable in field-portable instrumentation because of a lack of computational power. The described innovative migration velocity-adaptive moving average method uses an optimal averaging window size and can be easily implemented with a microcont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Considering the separation conditions, the electro‐stacking effect was not the only measure that helped achieving superior LOQ for the CE methods described in the literature. Special data conditioning that filters out the noise in the electropherogram adaptively to the peak migration time was applied for the electropherograms . It was observed that S/N ratio increased 5.8 and 6 times for the nisin 1 and nisin 2 peaks correspondingly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the separation conditions, the electro‐stacking effect was not the only measure that helped achieving superior LOQ for the CE methods described in the literature. Special data conditioning that filters out the noise in the electropherogram adaptively to the peak migration time was applied for the electropherograms . It was observed that S/N ratio increased 5.8 and 6 times for the nisin 1 and nisin 2 peaks correspondingly.…”
Section: Resultsmentioning
confidence: 99%
“…After analysis, vials containing BGE were replenished. The sensitivity of the analysis was enhanced using special data conditioning following the Migration Velocity Adaptive Moving Average method . Using this method, the peaks in the electropherograms are smoothed adaptively using optimal smoothing average window size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some attempts to reduce thermal and electrical effects on the baseline fluctuations using differential C4D measurement were demonstrated . Computerized method based on migration velocity‐adaptive moving average method for improving the sensitivity of the developed system has been developed and applied . In C4D and conventional conductivity measurements, the reading depends on the temperature .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis that can be performed in situ provides several advantages: (i) reduces analysis errors due to the fact that sample transportation is not needed, and chemical degradation is avoided, and (ii) reduces the duration of the total analytical process [5]. Several chemical analyftical techniques have been applied, or are being developed for field-portable or autonomous applications: (i) liquid chromatography [6,7], (ii) capillary electrophoresis [8][9][10][11], (iii) digital microfluidics [12] and (iv) electrochemical analysis [13]. Designing portable or autonomous instruments can be problematic due to the following reasons: (i) such instrumentation has the limited battery power supply, (ii) a low number of mechanical and moving parts must be used in the design, and (iii) such instrumentation is susceptible to changing environment and especially temperature fluctuations [10,14].…”
Section: Introductionmentioning
confidence: 99%